THE INFLUENCE OF PRINCIPAL LEADERSHIP, TEACHER MOTIVATION, WORK CULTURE, WORK ENVIRONMENT, TEACHER WELFARE AND LOCAL COMMUNITY SUPPORT ON SCHOOL PERFORMANCE IN PRIVATE JUNIOR HIGH SCHOOLS IN BATAM CITY - Mega Heriyanto; Sri Langgeng Ratnasari; Hermansah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to determine the effect of principal leadership, teacher motivation, work culture, work environment, teacher welfare, and local community support on school performance in private junior high schools in Batam City, both partially and simultaneously. The method used is quantitative analysis by distributing questionnaires to private junior high school teachers in Batam City. Statistical tests carried out include validation and reliability, as well as multiple linear regression analysis using the SPSS 21 program. Quantitative data were collected through questionnaires distributed to 120 respondents, consisting of principals and teachers, with a population of 200. Sampling was carried out using the product moment formula with an error rate of 5% with a non-probability sampling method, namely cluster sampling, with an error rate of 5%. The results of the analysis showed that all questionnaire items were valid (p <0.05) and the reliability reached 0.87. The results of multiple linear regression showed a calculated R value of 0.84, while the R table at α = 0.05 was 0.30. Thus, the hypothesis is accepted because the calculated R> R table. The R² value of 0.71 indicates that 71% of the variation in school performance can be explained by the six independent variables. The F test produces a significance value of 0.000, which confirms that the regression model is significant at the α = 0.05 level. The t test shows that all independent variables have a p value <0.05, indicating a significant effect both partially and simultaneously on school performance. This study is compared with three previous relevant studies, namely research by Sri Langgeng Ratna Sari (2020), which discusses the effect of leadership on motivation; Rahman (2021), which examines the impact of work culture on performance; and Putri (2022), which investigates the relationship between teacher welfare and school performance. These findings show consistency in the results related to the influence of managerial factors on educational performance.